E02 Selective thalamic volume loss in huntington's disease-like 2; a novel MRI finding compared to huntington's disease. (September 2018) - Anderson, David G; Haagensen, Mark; Ferreira-Correia, Aline; Pierson, Ronald; Carr, Jonathan; Krause, Amanda; Margolis, Russell L
Abstract : Background: Huntington's Disease-Like 2 (HDL2) is one of the most common Huntington's Disease (HD) phenocopies. Clinical similarities between these genetically different diseases are remarkable and the MRIs between them have been indistinguishable. Objective: To compare MRIs between HDL2 and HD against unaffected controls using semiautomated volumetric analysis and morphometry. Methods: Participants with a mixed or African ancestry were enrolled from an area with the world's highest frequency of HDL2. All MRIs were performed on 1.5T and processed by Brain Image Analysis, LLC as described in previous HD studies. Analysis was done blind to the participants diagnosis. Results: There were nine HDL2, ten HD, and 9 controls enrolled. Volume loss was greater in HDL2 patients when compared to HD, however significantly more thalamic volume loss was seen in HDL2 relative to HD and controls when controlled across multiple covariances. Conclusion: Our findings suggest selective thalamic atrophy in HDL2 compared to HD.